Modeling and optimization of compaction pressure, binder percentage and retention time in the production process of carbonized sawdust-based biofuel briquettes using response surface methodology (RSM) - Junior Maimou Nganko; Ekoun Paul Magloire Koffi; Prosper Gbaha; Alpha Ousmane Toure; Moustapha Kane; Babacar Ndiaye; Mamadou Faye; Willy Magloire Nkounga; Claudine Tiogue Tekounegning; Echua Elisabeth Jasmine Bile; Kouassi Benjamin Yao (Heliyon, 2024)
The importance of parameters such as compaction pressure, binder percentage and retention time and their interaction in the production of carbonized briquettes for domestic or industrial use cannot be overestimated, as they have a considerable impact on the properties of the resulting briquettes. This study used Box-Behnken Response Surface Methodology (RSM) and Analysis Of Variance (ANOVA) to show how the above parameters and their interactions significantly influence the Higher Heating Value (HHV), ash content and Impact Resistance Index (IRI) of the biofuels obtained. The briquettes are characterized in accordance with American Society for Testing and Materials ASTM D-(5865 and 3172). IRI is determined by the drop test. The Niton XLT900s X-ray fluorescence spectrometer is used for mineralogical analysis. The peel starch used as a binder is characterized by the Association of Official Agricultural Chemists standard. This starch has a starch purity of 89.8 %, an HHV of 13974 kJ/kg, a protein content of 4.79 % and a sugar content of 1.3 %. The HHV of the biofuels ranged from 23783 to 26050 kJ/kg, their ash content from 2.86 to 5.24 %, and the IRI from 136.36 to 500 %. The significant effect of binder on these results is confirmed (p < 0.05). The Standard deviations of ± 21.425 kJ/kg, ± 0.021 % and ± 2.121 % were obtained between the experimental values and those of the mathematical models developed to predict HHV, ash content and IRI. The optimum parameters for industrial biofuel production correspond to a binder percentage of 10 %, a compaction pressure of 75 kPa and a retention time of 7.49 min. The experimental results under these conditions are: 25596 kJ/kg, 3.01 % and 375 % for HHV, ash content and IRI. In correlation with the absence of certain heavy metals, the study confirms that the briquettes produced are suitable for domestic use.